Aproximaciones al concepto de imaginario social. (2019)
This article offers a series of elements to introduce the reader to the understanding of the concept of social imaginary. This is a polyvalent concept with an outstanding tradition that deserves a detailed approach and that, at present, is nourished by perspectives that enrich and nuance it. In this situation, the references of its discernment are placed, which in turn differentiates it from concepts usually located as equivalent. The central ideas developed by Cornelius Castoriadis, Manuel Antonio Baeza and Juan Luis Pintos, who are part of two intellectual currents, are also presented. Finally, the text highlights the conceptual richness of the social imaginary and its usefulness in the theoretical-methodological and practical debate of social science and aims to stimulate the discussion and interest around it. In particular, it emphasizes the possibility that it opens to counteract the stagnation produced by the eagerness to propose and make use of defined and closed concepts, a sort of commonplace of “true science”. Moreover, the search offers innovative paths for the exercise of social science in a context as malleable and ductile as the contemporary one and that, when placed on the Latin American and national scenario, finds contradictory and even irrational views